Pengalaman Imitasi Budaya Fashion Streetwear Korea Pada Kaum Remaja - Rika Oktariana; Anis Endang; Yanto Yanto (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Cultural imitation is a form of adaptation or change in behavior and lifestyle that is reflected in a particular culture. In this context, the experience of imitation of Korean streetwear fashion culture among teenagers is an interesting phenomenon for further research. The concept of “Cultural Imitation” refers to the process by which individuals or groups imitate or adopt cultural aspects of another culture into their own lives. Korean Streetwear fashion carries Korean cultural values ​​that influence the character, values ​​and behavior of teenagers, so it needs to be analyzed in depth. The selection of this problem allows the exploration of psychological and sociological dimensions. From a psychological perspective, the research will highlight the influence of Korean streetwear fashion on teenagers' identity and self-concept. This research aims to determine the experience and impact of imitation of Korean streetwear fashion culture on teenagers in Indonesia. In this way, it is hoped that this research can contribute to an in-depth understanding of the role of media and culture in shaping the character and behavior of teenagers, and can be used as a basis for formulating policies that support the positive development of teenagers in this digital era. This research method is a qualitative descriptive approach chosen because this research aims to provide an in-depth and comprehensive picture of the experience of imitating Korean streetwear fashion culture among teenagers. The results of the research above explain that encouragement from oneself and support from the environment can strengthen and motivate someone to imitate Sashfir's fashion style. When there is more encouragement and support for Sashfir's fashion style that he wants to imitate, the stronger a person's desire to imitate that fashion will become. The source of the directing process itself is encouragement, it could be because he wants to imitate, it could also be that he sees people imitating and becomes interested, and there is also encouragement from the surrounding environment that supports him to imitate because he feels it is suitable to imitate Sashfir's fashion style because they think it suits his personality